2003
DOI: 10.1093/humrep/deg347
|View full text |Cite
|
Sign up to set email alerts
|

Tubal damage in infertile women: prediction using chlamydia serology

Abstract: CATs are of predictive value in the detection of tubal damage and are quantitatively related to the severity of damage. For practical clinical purposes, Chlamydia serology is useful mainly as a screening test for the likelihood of tubal damage in infertile women and may facilitate decisions on which women should proceed with further investigations without delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 44 publications
10
62
1
2
Order By: Relevance
“…Price et al used a statistical modelling approach to estimate that 45% (credible interval 28%, 62%) of tubal infertility cases are caused by chlamydia [138]. This estimate is similar to some obtained directly from case-control studies but has the advantage that the method takes into account uncertainty about the sensitivity and specificity of chlamydia antibody tests [139] and the likelihood that chlamydia antibody levels are higher in women with tubal factor infertility that was caused by chlamydia that in women with tubal factor infertility caused by another organism or condition in women with coincidental exposure to chlamydia [161]. The attributable fraction could change over time if either prevalence or the strength of association change.…”
Section: Ectopic Pregnancy and Tubal Infertilitysupporting
confidence: 66%
“…Price et al used a statistical modelling approach to estimate that 45% (credible interval 28%, 62%) of tubal infertility cases are caused by chlamydia [138]. This estimate is similar to some obtained directly from case-control studies but has the advantage that the method takes into account uncertainty about the sensitivity and specificity of chlamydia antibody tests [139] and the likelihood that chlamydia antibody levels are higher in women with tubal factor infertility that was caused by chlamydia that in women with tubal factor infertility caused by another organism or condition in women with coincidental exposure to chlamydia [161]. The attributable fraction could change over time if either prevalence or the strength of association change.…”
Section: Ectopic Pregnancy and Tubal Infertilitysupporting
confidence: 66%
“…However, none of the chlamydial serological results were significantly associated with tubal infertility in the validation infertility clinic group (group 4). This result was inconsistent with most published studies, where chlamydial serology is typically significantly associated with tubal infertility (Akande et al, 2003;Mehanna et al, 1995;Claman et al, 1997;Land et al, 2003). However, it is possible that this is because the study included women with unknown tubal status in the comparison group, who would often be excluded in studies like this one.…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown that CAT is more accurate in predicting distal tubal pathology, instead of unspecified tuboperitoneal abnormalities or proximal tubal occlusion [11]. Moreover, in studying the implications of different cutoff titres for a positive test, it has been noted that increasing the cutoff titre will improve the specificity, at the expense of sensitivity [7,12,15]. In patients with laparoscopically detected tubal pathology but negative antibody titres, diminished antibody titres related to time has been considered by some authors but not by others [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, both methods are costly and invasive, and therefore unsuitable for screening on a large scale. Since tubal pathology and infertility have been associated with asymptomatic Chlamydia trachomatis infections in the past, chlamydia antibody testing (CAT) in serum has been introduced as a screening method for tubal factor subfertility [7][8][9][10]. Hence the development of a simple and reliable assay for the detection of C. trachomatis antibodies is essential.…”
Section: Introductionmentioning
confidence: 99%